Intrauterine aortic angioplasty - Marantz, Pablo; Granja, Miguel; Aiello, Horacio; Trentacoste, Luis; Izbizky, Gustavo; Elias, Diego; Otaño, Lucas (Revista del Hospital Italiano de Buenos Aires, 2006)
.